2017
DOI: 10.1039/c7ta04382a
|View full text |Cite
|
Sign up to set email alerts
|

Growth of NiMn LDH nanosheet arrays on KCu7S4 microwires for hybrid supercapacitors with enhanced electrochemical performance

Abstract: The quasi-paralleled and interlaced nanosheet arrays of NiMn layered double hydroxides are successfully grown on KCu7S4 microwires with quasi-one-dimensional channel by tuning the concentration of the metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…Moreover, due to the features of multiple oxidation states, high electrical conductivity, tunable ratio of metallic elements, high theoretical capacitances, environment‐friendly, and low cost, 2D LDHs also have been regarded as a promising candidate in electrochemical energy‐storage electrodes . Huang et al reported a template‐assisted electrodeposition method to synthesize nickel–cobalt (Ni–Co) LDH shell with the Ni–Co metallic core (Ni–Co@Ni–Co LDH) on carbon fiber cloth (CFC) to form a structure of Ni–Co@Ni–Co LDH nanotube array/CFC .…”
Section: Pristine 2d Materials For Micro‐supercapacitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, due to the features of multiple oxidation states, high electrical conductivity, tunable ratio of metallic elements, high theoretical capacitances, environment‐friendly, and low cost, 2D LDHs also have been regarded as a promising candidate in electrochemical energy‐storage electrodes . Huang et al reported a template‐assisted electrodeposition method to synthesize nickel–cobalt (Ni–Co) LDH shell with the Ni–Co metallic core (Ni–Co@Ni–Co LDH) on carbon fiber cloth (CFC) to form a structure of Ni–Co@Ni–Co LDH nanotube array/CFC .…”
Section: Pristine 2d Materials For Micro‐supercapacitorsmentioning
confidence: 99%
“…The excellent pseudocapacitive performance was benefited from the abundant structural defects and accessible active sites created on the heterostructures as well as the synergetic effect that greatly facilitated charge transfer rates, thus making the as‐constructed asymmetric supercapacitor exhibited a wide potential window, high energy density, long cycling life, and great rate capability. Zhang and co‐workers designed a 2D‐on‐1D architecture via growing nickel–manganese (Ni–Mn) LDHs nanosheet arrays with quasi‐paralleled morphology on a 1D KCu 7 S 4 microwires (Figure c) . The as‐fabricated electrodes exhibited excellent electrochemical performance of an excellent rate capability and high specific capacitance, thus making the constructed micro‐supercapacitors present outstanding cycle stability as well as improved power and energy density.…”
Section: Architectural Design Of 2d Electrode Materialsmentioning
confidence: 99%
“…When hydroxyl act as weak field ligands, Mn 3 + are in the high spin state, which leading to instability of NiMn LDH, Mn 3 + are easily oxidized to Mn 4 + , we can also observe that the characteristic peak of Mn 4 + exists at 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 around 647 eV. [28,[35][36][37] Additionally, the EDS mapping of UNML nanosheets ( Figure S2a-d) shows the homogeneous distribution of Ni, Mn and O elements.…”
Section: Resultsmentioning
confidence: 65%
“…Guo et al showed a core/shell design using porous NiCo 2 O 4 nanowires as core and NiMn LDH nanosheets as shell by co-precipitation method using urea at 80 °C for 80 min [ 29 ]. They also applied the same method to deposit NiMn LDH onto the surface of KCu 7 S 4 microwires with urea at 80 °C for 2 h [ 30 ]. Zhao et al reported that NiMn LDHs were prepared by the reaction of hexamethylenetetramine with metal salts at 90 °C under stirring for 4 h [ 28 ].…”
Section: The Synthesis Methods Of Nimn Ldhsmentioning
confidence: 99%